Peran Penguatan Literasi Numerasi (Mata Pelajaran Matematika dan Non-Matematika) terhadap Peningkatan Sikap Matematis Siswa Madrasah Ibtidaiyah - Santoso, Agus; Widyastuti, Suciati Rahayu (LPPM UNU CIREBON, 2024)
This study aims to the role of strengthening numeracy literacy (mathematics and non-mathematics subjects) in improving the mathematical attitudes of elementary madrasah students. In the current educational context, numeracy literacy is very important to build a strong conceptual understanding among students. The purpose of this study is to identify and analyze how numeracy literacy reinforcement can improve students' mathematical attitudes and to develop effective implementation recommendations. The method used in this study is a literature study, which includes an analysis of various literature and previous research on numeracy literacy and mathematical attitudes. The population in this literature study includes all literature related to numeracy literacy and mathematical attitudes. The results of this literature review are expected to provide in-depth insight into the importance of numeracy literacy in developing students' mathematical attitudes and guide educators in designing a more effective curriculum. In conclusion, implementing numeracy literacy reinforcement has been proven to have the potential to improve students' mathematical attitudes, so it needs to be a focus in developing teaching strategies at Madrasah Ibtidaiyah. Keywords: Impact, Literacy, Numeracy, Attitude, Mathematics